Coats’ Disease Masquerading as Retinoblastoma: Diagnostic Dilemmas - Prabowo, Septian Dwi; Lutfi, Delfitri; Fauziah, Dyah (Journal of Neonatal Surgery, 2025)
Coats' disease is one of the most difficult differential diagnoses of intraocular mass especially retinoblastoma in early childhood. Despite comprehensive diagnostics, retinoblastoma remains possible, and enucleation appears necessary in uncertain cases with poor visual prognosis. This case, reports a 3-year-old boy with leukocoria, recurrent redness, and strabismus in the right eye for 1 year. Due to the results of ultrasonography and CT-scan examination, a retinoblastoma was suspected, so enucleation with pathology examination was performed. The findings in pathology examination were consistent with Coats’ disease and negative for retinoblastoma. Although it is difficult to distinguish between retinoblastoma and coats’ disease, it is necessary to initiate a comprehensive examination of clinical characteristics and ancillary test to rule out retinoblastoma, which needs to be distinguished from a variety of benign mimicking lesions to ensure the appropriate therapy. A pathologist’s confirmation and discussion are required for further appropriate treatment due to the unexpected pathology result.